Executive Summary of the Early-Onset Breast Cancer Evidence Review Conference. Issue 6 (June 2020) - Chelmow, David; Pearlman, Mark D.; Young, Amy; Bozzuto, Laura; Dayaratna, Sandra; Jeudy, Myrlene; Kremer, Mallory E.; Scott, Dana Marie; O'Hara, Julia Sage
Abstract : The Centers for Disease Control and Prevention launched the Bring Your Brave campaign to increase knowledge about early-onset breast cancer, defined as breast cancer in women aged 18–45 years. The American College of Obstetricians and Gynecologists convened a panel of experts in breast disease from the Society for Academic Specialists in General Obstetrics and Gynecology to review relevant literature, validated tools, best practices, and practice guidelines as a first step toward developing educational materials for women's health care providers about early-onset breast cancer. Panel members conducted structured literature reviews, which were then reviewed by other panel members and discussed at an in-person meeting of stakeholder professional and patient advocacy organizations in April 2019. This article summarizes the relevant literature, existing guidance, and validated tools to guide health care providers in the prevention, early detection, and special considerations of early-onset breast cancer. Substantive knowledge gaps were noted and summarized to provide guidance for future research. Abstract : Evidence for early-onset breast cancer prevention, diagnosis, and special issues from the early-onset breast cancer evidence review conference is summarized.